Effect of Elective Cesarean Section on Children's Obesity From Birth to Adolescence: A Systematic Review and Meta-Analysis - Zhang, Shanshan; Qin, Xiaoyun; Li, Peixuan; Huang, Kun (Frontiers in Pediatrics, 2022)
Background: Elective cesarean section (ECS) is the most common reason for the increasing cesarean section rate worldwide, as is reported to be related with adverse short-term and long-term outcomes in both mothers and infants. Findings on the association between elective cesarean section (ECS) and overweight and obesity in children are controversial in recent studies. Therefore, we conducted a systematic review and meta-analysis to examine the effect of ECS on offspring’s overweight and obesity. Methods: Pubmed, Science Direct, Web of Science, CNKI (China National Knowledge Infrastructure), Wanfang Database (in Chinese) and China Biology Medicine disc databases were searched using different combinations of three groups of keywords “ elective cesarean section”, “overweight/obesity” and “children”. Nine cohort studies and 11 independent risk estimates were finally identified. Results:We have observed significant association between ECS and children’s obesity, the total pooled risk ratio (RR) being 1.10 (95% CI: 1.01-1.18; I2 32.4%). In subgroup analysis, ECS was found to be associated with the occurrence of obesity in preschoolers (RR=1.12, 95% CI 1.02–1.22; I2 16.8%). Furthermore, it revealed that ECS was related with the high risk of children’s obesity where the rate of ECS exceeded 10%. No significant association was observed between ECS and children’s overweight, and the RR was 1.12 (95% CI 0.94-1.30; I2 55.6%). Conclusions:Overall, it indicated that children born via elective cesarean section had an increased risk of later-life obesity. Given the global increase in childhood obesity, our findings would provide evidence-based reference for early life intervention on children’s obesity.